Learning Style Adaptation of Generation Z to Short Educational Videos on Social Media - Veti Rahma (Journal of Education in Specific Purpose, 2025)
The rapid growth of digital technology and social media has significantly influenced how Generation Z engages with educational content. This study explores how Gen Z high school students adapt their learning styles to short educational videos available on platforms such as TikTok, YouTube Shorts, and Instagram Reels. Using a qualitative descriptive research design, data were collected through interviews, focus group discussions, and questionnaires involving 30 students from urban senior high schools. The findings reveal that Gen Z learners prefer visual, fast-paced, and interactive content, with short videos serving as effective tools for reinforcing understanding and engaging attention. Students reported that these microlearning formats support their multitasking habits and align with their digital media consumption patterns. However, concerns emerged regarding content credibility and distraction when educational material is mixed with entertainment. The study highlights the potential of short-form video as a supplementary learning tool in hybrid and post-pandemic educational environments. It also identifies a gap in existing research concerning long-term impacts and learning outcomes, suggesting a need for further studies. The insights provided can inform educators, content developers, and policymakers in designing more effective digital learning strategies tailored to Gen Z preferences.